Sensitivitas gender pendidik pesantren di Purwokerto - Farichatul Maftuchah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2023)
The issue of gender sensitivity is still a hot topic of discussion today. Therefore, this research aims to reveal the forms of gender sensitivity of pesantren educators in Purwokerto. The method used in this study is descriptive qualitative, with aspects of field studies. The research subjects are nine Islamic boarding schools’ partners with State Islamic University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto. From the nine pesantren, at least two educators were taken as research subjects. The results of this study indicate that the forms of gender sensitivity in partner pesantren education are as follows: understanding of the concept of gender, the functions of men and women in the private and public spheres, interpretation of religion (inheritance), profession, and proportionality.